EIDOSCOPE: particle acceleration at plasma boundaries - Vaivads, A; Andersson, G; Bale, S; Cully, C; De Keyser, J; Fujimoto, M; Grahn, S; Haaland, S; Ji, H; Khotyaintsev, Y; Lazarian, A; Lavraud, B; et al. (2012)
We describe the mission concept of how ESA can make a major contribution to the Japanese Canadian multi-spacecraft mission SCOPE by adding one cost-effective spacecraft EIDO (Electron and Ion Dynamics Observatory), which has a comprehensive and optimized plasma payload to address the physics of particle acceleration. The combined mission EIDOSCOPE will distinguish amongst and quantify the governing processes of particle acceleration at several important plasma boundaries and their associated boundary layers: collisionless shocks, plasma jet fronts, thin current sheets and turbulent boundary layers. Particle acceleration and associated cross-scale coupling is one of the key outstanding topics to be addressed in the Plasma Universe. The very important science questions that only the combined EIDOSCOPE mission will be able to tackle are: 1) Quantitatively, what are the processes and efficiencies with which both electrons and ions are selectively injected and subsequently accelerated by collisionless shocks? 2) How does small-scale electron and ion acceleration at jet fronts due to kinetic processes couple simultaneously to large scale acceleration due to fluid (MHD) mechanisms? 3) How does multi-scale coupling govern acceleration mechanisms at electron, ion and fluid scales in thin current sheets? 4) How do particle acceleration processes inside turbulent boundary layers depend on turbulence properties at ion/electron scales? EIDO particle instruments are capable of resolving full 3D particle distribution functions in both thermal and suprathermal regimes and at high enough temporal resolution to resolve the relevant scales even in very dynamic plasma processes. The EIDO spin axis is designed to be sun-pointing, allowing EIDO to carry out the most sensitive electric field measurements ever accomplished in the outer magnetosphere. Combined with a nearby SCOPE Far Daughter satellite, EIDO will form a second pair (in addition to SCOPE Mother-Near Daughter) of closely separated satellites that provides the unique capability to measure the 3D electric field with high accuracy and sensitivity. All EIDO instrumentation are state-of-the-art technology with heritage from many recent missions. The EIDOSCOPE orbit will be close to equatorial with apogee 25-30 RE and perigee 8-10 RE. In the course of one year the orbit will cross all the major plasma boundaries in the outer magnetosphere; bow shock, magnetopause and magnetotail current sheets, jet fronts and turbulent boundary layers. EIDO offers excellent cost/benefits for ESA, as for only a fraction of an M-class mission cost ESA can become an integral part of a major multi-agency L-class level mission that addresses outstanding science questions for the benefit of the European science community. © 2011 Springer Science+Business Media B.V.